Where Now for Visible Unity?: An Ecumenical Comparison of the Letter to the Ephesians and the Gospel of John - Heckel, Ulrich (The ecumenical review, 2024)
Against the background of the Sixth World Conference on Faith and Order, which will take place in 2025 around the theme “Where now for visible unity?” this article explores the marks of visible unity set out in the Gospel of John and the Letter to the Ephesians. The two texts show an astonishing convergence. Following a biblical exegesis, the article concludes that discussions about the visible unity of the church need first to establish the similarities and differences in the understanding of the eucharist. The question of the understanding of ministry must first be clarified in a differentiated way. If the unity of the church consists in the confessional fellowship of believers, then it is not the institutionalized uniformity of the ministerial structure that is decisive, but rather unity in faith in the one shepherd and Lord as head of the church and Saviour of the world. Unity becomes visible above all in common prayer and worship, not only within different traditions as in Ephesus, but even more so when different church traditions celebrate ecumenically.